A Spatial Integration Analysis of the Regional Fertilizer Markets in the Philippines - Ivory Myka R. Galang (Philippine Institute for Development Studies (PIDS), 2014)
Fertilizer, which is an important production input, holds a significant share in total cost of production for some crops. Based on the available fertilizer price data, it can be observed that price levels vary greatly across regions. To help determine whether or not this variability is alarmingly high, a spatial market integration analysis was done. Based on the Granger causality test, it is found that the price in one region either causes or affects prices in another region. The cointegration test suggests that regional markets are integrated. Long-run relationships are also shown to be statistically significant. The finding that regional fertilizer markets in the Philippines are integrated is consistent with the absence of market power in the fertilizer industry. The number of market players in the industry makes it highly unlikely for one or few dealers of fertilizer to control the market price of fertilizer.
Keywords: 330; Philippines; fertilizer; spatial market integration; Granger causality; Johansen cointegration test